Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian Makanan Pendamping Asi (MP -ASI ) Pada Anak Usia 6 - 24 Bulan Di PBM Susi Rini Safitri Kab.Simalungun Tahun 2023 - Susi Rini Safitri; Basaria Manurung; Emma Dosriamaya Noni Br Simanjuntak (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Infancy between the ages of 6-24 months is a golden age for child growth and development. This period is a good opportunity for parents to strive for optimal child growth and development. One effort that parents can make to achieve this is through good and correct parenting patterns given to children. This study aims to determine the Relationship between Mother's Knowledge and Attitudes with the Provision of Complementary Foods (MP-ASI) to Children Aged 6-24 Months at PBM Susi Rini Safitri, Simalungun Regency in 2023. This type of research is an analytical survey study with a cross-sectional method approach. The population is all mothers who have children aged 6-24 months as many as 42 people. The number of samples used was 42 people obtained using the Total sampling technique. The data analysis technique used chi square. the results obtained in this study are from 42 respondents, there is a relationship between maternal attitudes and the Provision of Complementary Food for Breast Milk (MP-ASI) in Children Aged 6-24 Months shows that the p value = 0.000 <0.05. there is a relationship between maternal knowledge and the Provision of Complementary Food for Breast Milk (MP-ASI) in Children Aged 6-24 Months shows that the p value = 0.012 <0.05. It is recommended for Health Workers to increase counseling related to the Occurrence of Anemia in Pregnant Women.